Analysis of The Relationship Between TQM and MBS for Educational Needs in The 21 St Century - Nurhajati, Nurhajati; Pertiwi, Santhi; R. Madhakomala, R. Madhakomala (Jurnal Edusci, 2025)
This study aims to describe and analyze the relationship between TQM and SBM for education needs in the 21st century. This research uses a literature study method by observing various documents from books and journals. The literature study focuses on researching literature related to total quality management, SBM, and students' character in the 21st century. Data collection is carried out by collecting literature data, reading, recording, and managing research results objectively, systematically, analytically, and critically by looking at the year of publication and the most up-to-date research. The results of this study show that TQM and SBM have an essential role in education in the 21st century. This is because TQM and MBS provide enthusiasm for education managers to continue to adapt, improve quality, and compile what the educational institution needs. TQM and MBS have a good relationship in the management of education in the 21st century.